EFFECTIVENESS OF GROUP COUNSELING SERVICES USING MOTIVATIONAL INTERVIEWING TECHNIQUE TO IMPROVE GRIT IN FINAL SEMESTER STUDENTS: Final Year Students, Grit, Group Counseling, Motivational Interviewing - Nur Jihan Maimanah; Nefi Darmayanti (SOSIOEDUKASI, 2025)
This study aims to determine the effectiveness of group counseling services using the Motivational Interviewing technique in increasing grit among final-year students. The research employed a quantitative approach with a pre-experimental method using a One Group Pretest-Posttest design. The participants consisted of 8 eighth-semester BKPI-2 students who were selected based on low grit levels and their willingness to participate in group counseling. The data collection instrument used a grit scale that measured two main aspects: perseverance and consistency of interest. The analysis results showed a significant increase in grit scores before and after the intervention, as evidenced by the Wilcoxon Signed Rank Test (sig. value = 0.012 < 0.05). Thus, group counseling services using the Motivational Interviewing technique proved to be effective in enhancing grit among final-year students.